Basin‐scale assessment of the land surface water budget in the National Centers for Environmental Prediction operational and research NLDAS‐2 systems. Issue 6 (25th March 2016) - Xia, Youlong; Cosgrove, Brian A.; Mitchell, Kenneth E.; Peters‐Lidard, Christa D.; Ek, Michael B.; Brewer, Michael; Mocko, David; Kumar, Sujay V.; Wei, Helin; Meng, Jesse; Luo, Lifeng
Abstract: The purpose of this study is to evaluate the components of the land surface water budget in the four land surface models (Noah, SAC‐Sacramento Soil Moisture Accounting Model, (VIC) Variable Infiltration Capacity Model, and Mosaic) applied in the newly implemented National Centers for Environmental Prediction (NCEP) operational and research versions of the North American Land Data Assimilation System version 2 (NLDAS‐2). This work focuses on monthly and annual components of the water budget over 12 National Weather Service (NWS) River Forecast Centers (RFCs). Monthly gridded FLUX Network (FLUXNET) evapotranspiration (ET) from the Max‐Planck Institute (MPI) of Germany, U.S. Geological Survey (USGS) total runoff ( Q ), changes in total water storage (d S /d t, derived as a residual by utilizing MPI ET and USGS Q in the water balance equation), and Gravity Recovery and Climate Experiment (GRACE) observed total water storage anomaly (TWSA) and change (TWSC) are used as reference data sets. Compared to these ET and Q benchmarks, Mosaic and SAC (Noah and VIC) in the operational NLDAS‐2 overestimate (underestimate) mean annual reference ET and underestimate (overestimate) mean annual reference Q . The multimodel ensemble mean (MME) is closer to the mean annual reference ET and Q . An anomaly correlation (AC) analysis shows good AC values for simulated monthly mean Q and d S /d t but significantly smaller AC values for simulated ET. Upgraded versions of the models utilized in the research side of NLDAS‐2 yield largely improved performance in the simulation of these mean annual and monthly water component diagnostics. These results demonstrate that the three intertwined efforts of improving (1) the scientific understanding of parameterization of land surface processes, (2) the spatial and temporal extent of systematic validation of land surface processes, and (3) the engineering‐oriented aspects such as parameter calibration and optimization are key to substantially improving product quality in various land data assimilation systems. Key Points: Evaluation of the water budget components in NCEP operational and research NLDAS‐2 systems Focus on 12 National Weather Service's River Forecast Centers First using USGS HUC8 monthly runoff and gridded FLUXNET ET products to evaluate NLDAS‐2 products